Apolipoprotein E ε4 Is Associated With the Development of Incident Dementia in Cerebral Autosomal Dominant Arteriopathy With Subcortical Infarcts and Leukoencephalopathy Patients With p.Arg544Cys Mutation - Lee, Jung Seok; Ko, Keun Hyuk; Oh, Jung-Hwan; Kim, Joong-Goo; Kang, Chul-Hoo; Song, Sook-Keun; Kang, Sa-Yoon; Kang, Ji-Hoon; Park, Joon Hyuk; Koh, Myeong Ju; Lee, Ho Kyu; Choi, Jay Chol (Frontiers in Aging Neuroscience, 2020)
Background and Purpose To identify clinical, laboratory, and magnetic resonance imaging (MRI) features in predicting incident stroke and dementia in Korean patients with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL). Materials and Methods We enrolled 87 Korean CADASIL patients who had undergone baseline clinical, laboratory, and MRI examinations between March 2012 and February 2015. The primary outcome of this study is the occurrence of stroke and dementia during the study period. The occurrence of incident stroke was confirmed by neuroimaging study, and dementia was defined by the diagnostic and statistical manual of mental disorders, fourth edition, criteria. Results Of the 87 patients, 57.5% were men, and the mean age was 63 ± 13 years (range 34–90 years), and 82 patients (94.3%) had p.Arg544Cys mutation. During an average follow-up of 67 months (interquartile range: 53–69 months), incident stroke occurred in 14 of 87 patients (16.1%) and incident dementia in 7 of 70 non-demented patients (10.0%). In adjusted analysis, increased systolic blood pressure was associated with increased risk of incident stroke [for every 10-mmHg increase; hazard ratio, 1.44 (1.02–2.03)]. Apolipoprotein E ε4 genotype was associated with an increased risk of incident dementia [hazard ratio, 10.70 (1.27–89.88)]. Conclusion In this study, apolipoprotein E ε4 genotype was associated with the development of incident dementia, and higher blood pressure was associated with increased risk of incident stroke in CADASIL patients with predominant p.Arg544Cys mutation.